Antonio Gramsci: a biographical study of the thinker’s life (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2025)
This paper presents a critical review of the literature on the biography of Antonio Gramsci (1891-1937). Marxist philosopher, writer, political theorist, journalist, literary critic, linguist, historian, politician and Italian translator, Gramsci was a co-founder of the Communist Party of Italy and author of the Prison Notebooks, written during his imprisonment by the fascist regime of Benito Mussolini. Through a critical literature review, the study highlights the importance of reliable sources in the construction of biographies, discussing discrepancies in historical records and the influence of different interpretations on their trajectory. In addition, the research addresses little-mentioned aspects of his life, such as his condition as a disabled person and the political circumstances surrounding both his imprisonment and that of his father, Francesco Gramsci. The analysis seeks to fill historiographical gaps and provide a well-founded view of Gramsci’s life, highlighting his relevance for academic studies in thirty-five areas of knowledge in Brazil. The paper also features images of the Sardinian thinker and his family.Keywords: Antonio Gramsci. Biography. Historiographical sources.